Implementation of Internet of Things Mesh Network System in Improving Agricultural Production (International Journal of Food and Nutritional Sciences, 2022)
Agriculture is a profession that is evolving with technologies as the world's population grows and food need rises. The rising food demand necessitates an increase in food output derived from cereals, vegetables, fruits, and so on. Agriculture is linked to a variety of enterprises such as animal husbandry, sericulture, horticulture, poultry farming, and so on. The "Internet of Things" (IoT) is evolving and is currently used in every industry, from banking to agriculture. The Internet of Things is used to automate agricultural processes such as irrigation, harvesting, monitoring, and so on. Agriculture that's also focused on research employs a variety of technologies. Various network systems utilized in agriculture are examined during the research. The research contributes to the advancement of agricultural technology, assisting farmers in increasing farm productivity. The analysis will result in a new manner of employing technology in which a person may do all duties from a single location.